Analisis Pengalaman, Strategi, Dan Tantangan Praktis UMKM Di Desa Kalukubula Kabupaten Sigi - Wulandari Wulandari; Muhammad Wandi Adriansa; Audietya Chantieka Aura; Nur Aini Bakhri; Desyah Nabilla; Indah Amalia; Nuraisyah Nuraisyah; Andi Maman Firmansyah; Fachrul Reza (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the experiences, strategies, and challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Kalukubula Village, Sigi Regency, Central Sulawesi. Using a qualitative approach, this research explores three distinct types of MSMEs: Zahra Collection Store (clothing retail), Q.Box (food stall), and a local tailoring business. Data were collected through in-depth interviews, field observations, and documentation of business activities. The findings reveal that MSME actors in this area encounter common challenges such as limited capital, restricted market access, and competition from outside products. However, they also implement various adaptive strategies, including leveraging social media for marketing, building customer loyalty through personalized service, and product development. This study contributes to understanding the dynamics of MSMEs in post-disaster areas and recommends the importance of government support in entrepreneurship training, financing access, and digital infrastructure development.